Alterations in neutrophil mRNA profiles in multiple sclerosis and identification of candidate genes for further investigation - Huining Zhang; Huining Zhang; Huining Zhang; Ruoyi Guo; Ruoyi Guo; Ruoyi Guo; Yusen Han; Yusen Han; Yusen Han; Zhichao Yao; Zhichao Yao; Zhichao Yao; et al. (Frontiers in Neurology)
IntroductionMultiple sclerosis (MS) is a chronic and debilitating inflammatory disease of the central nervous system (CNS), characterized by demyelination and neurodegeneration. Emerging evidence implicates neutrophils in MS pathogenesis, particularly through processes like neutrophil extracellular traps (NETs) formation and degranulation, which may exacerbate inflammation and autoimmunity.MethodsRNA sequencing of peripheral blood neutrophils from MS patients and healthy controls identified differentially expressed genes (DEGs). Pathway enrichment and protein–protein interaction (PPI) analyses highlighted potential biomarkers, validated using reverse transcription quantitative PCR (RT-qPCR) and enzyme-linked immunosorbent assay (ELISA).ResultsOur analysis identified 1,968 DEGs in neutrophils from MS patients, comprising 1,068 upregulated and 900 downregulated genes. Pathway enrichment analysis revealed significant involvement of immune processes, including antigen presentation, B and T cell receptor signaling, intracellular signaling cascades, and neutrophil degranulation. Notably, KEGG analysis highlighted a pivotal role for upregulated genes in neutrophil extracellular traps (NETs) formation, a process increasingly associated with autoimmunity. PPI network analysis pinpointed five key hub genes—LCN2, LTF, ELANE, CAMP, and CTSG—as central players in neutrophil-mediated immune modulation. Protein-level validation using ELISA confirmed elevated levels of LCN2, ELANE, CAMP, and CTSG, consistent with transcriptomic findings, further supporting their role as biomarkers. Subsequent RT-qPCR validation demonstrated robust diagnostic potential for these genes, with area under the curve (AUC) values of 0.952 (LCN2), 0.827 (LTF), 0.968 (ELANE), 0.950 (CAMP), and 0.862 (CTSG).DiscussionThese findings uncover a previously underappreciated role for neutrophils in MS pathogenesis, driven by alterations in gene expression linked to immune modulation and NET formation. The identified biomarkers, particularly ELANE and LCN2, demonstrate strong diagnostic potential, offering a new avenue for non-invasive MS diagnostics. Beyond clinical utility, this study highlights the importance of neutrophil-driven immune responses in MS, providing mechanistic insights into the complex interplay between innate and adaptive immunity in demyelinating diseases. Furthermore, these findings suggest that targeting neutrophil-specific processes, such as NETs formation and degranulation, could mitigate inflammatory damage and provide novel therapeutic approaches for MS treatment. These results lay the groundwork for future studies exploring therapeutic strategies targeting neutrophil functions in MS.